The Frequency Effect of the Motor Imagery Brain Computer Interface Training on Cortical Response in Healthy Subjects: A Randomized Clinical Trial of Functional Near-Infrared Spectroscopy Study - Lin, Qiang; Zhang, Yanni; Zhang, Yajie; Zhuang, Wanqi; Zhao, Biyi; Ke, Xiaomin; Peng, Tingting; You, Tingting; Jiang, Yongchun; Yilifate, Anniwaer; Huang, Wei; Hou, Lingying; et al. (Frontiers in Neuroscience, 2022)
Background The motor imagery brain-computer interface (MI-BCI) is now available in a commercial product for clinical rehabilitation. However, MI-BCI is still a relatively new technology for commercial rehabilitation application and there is limited prior work on the frequency effect. Methods Sixteen young healthy subjects (aged 22.94 ± 3.86 years) were enrolled in this randomized clinical trial study. Subjects were randomly assigned to a high-frequency group (HF group) and low-frequency group (LF group). The HF group performed MI-BCI training once per day while the LF group performed once every other day. All subjects performed 10 sessions of MI-BCI training. fNIRS measurement, Wolf Motor Function Test (WMFT), and BCI performance were assessed at baseline, mid-assessment (after completion of 5 BCI training sessions), and post-assessment (after completion of 10 BCI training sessions). Results The results from the two-way ANOVA of beta values indicated that GROUP, TIME, and GROUP × TIME interaction of the right primary sensorimotor cortex had significant main effects. The degree of activation was affected by training frequency, evaluation time point, and interaction. The activation of the left primary sensory-motor cortex was also affected by group (frequency) (P = 0.003). Moreover, the TIME variable was only significantly different in the HF group, in which the beta value of the mid-assessment was higher than that of both the baseline assessment (P = 0.027) and post-assessment (P = 0.001), respectively. Nevertheless, there was no significant difference in the results of WMFT between the HF group and the LF group. Conclusion The major results showed that more cortical activation and better BCI performance were found in the HF group relative to the LF group. Moreover, the within-group results also showed more cortical activation after 5 sessions of BCI training and better BCI performance after 10 sessions in the HF group, but no similar effects were found in the LF group. This pilot study provided an essential reference for the formulation of clinical programs for MI-BCI training in improvement for upper limb dysfunction.